Acquired ALK G1202R-, ALK I1171N-, or EML4-ALK-mediated resistance to ensartinib in lung adenocarcinoma but responded to lorlatinib: A case report - Ye, Zhifeng; Guo, Junhua (Frontiers in Oncology, 2023)
ALK rearrangement was identified as driver mutation in non-small-cell lung cancer (NSCLC). EML4-ALK is the most prevalent mutation in ALK alteration. Here we report a patient with lung adenocarcinoma was identified with EML4-ALK mutations when progressed on immune checkpoint inhibitor. The patient was treated with alectinib and get the PFS of 24 months. Then next generation sequencing identified multiple ALK mutations including ALK G1202R, I1171N, ALK-ENC1, EML4-ALK and TP53. Ensartinib was applied and got the PFS of 5 months. Then loratinib was treated and got PR. Until now the clinical benefit is still ongoing and achieved PFS more than 5 months. Our case may provide an evidence for the treatment choice of multiple ALK mutations including ALK I1171N.